SCREENING AND DETERMINATION OF CODEIN IN URINE SAMPLE - Priyasana, I Putu; Mayagita, Gusti Ayu Dinda; Rahmadinha, Vallina; Limba, Kristina Megi; Armitasari, Pande Made Nova (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 10 No 1 (2020): Indonesian Journal of Legal and Forensic Sciences, 2020)
Opiates are a group of narcotics that are often abused. Forensic experts play crucial roles in handling this. The screening test results that the sample containing opiate compounds. Confirmation testing is carrie out by using TE and TAE mobile phase systems. The error window values ??obtained in the TE and TAE systems are 10 and 8. Data collection of compounds in the range of hRfc 16.09 to 36.09 in the TE system obtained two compounds, Morphine and Codeine). And in the range of hRfc 25.1-9.1 also found Morphine and Codein compounds. The results of the correlation spectrum of the sample and spectrum in the library showed a correlation value of 0.99079 (TE system) and 0.99477 (TAE system) to the codeine compound. Determination testing is carried out using the TE mobile phase. This test results obtained that the concentration of codeine compounds is 20.88 ng / µL. These results indicate that the sample contains codeine in the lethal dose range.